Experimental study of spray combustion characteristics of air-blast atomizer - I. A. Ibrahim; T. M. Farag; M. E. Abdel-baky; A. K. Abd El-samed; H. M. Gad (Energy Reports, 2020)
In the present work, the characteristics of spray combustion an airblast atomizer with an innovative design were experimentally investigated. The flame was stabilized in a water-cooled combustor using air swirler. A test rig was manufactured to investigate the different operating conditions - which include the atomizing Air to Liquid fuel mass Ratio (ALR) of 5, 6, 7 and 8 and the elevated Atomizing Air Temperature (AAT) of 300, 350, 400, and 450 K. The spray combustion characteristics are represented in the form of axial and radial temperatures distributions, temperature gradients, visible flame length, and species concentrations. The axial and radial temperature distributions of flame were measured using the type R thermocouple. The species concentrations were measured by an infrared AO2000 series gas analyzer. The results indicate that the high-temperature combustion region is shifted upstream and outward and the flame length becomes shorter by increasing the value of both ALR and AAT. In addition, the NO concentration reaches its maximum values near the location of the maximum centerline axial temperature. Moreover, it was found that increasing the AAT leads to, on the one hand, decreasing the gas temperature, the and the CO concentrations at the combustor end, on the other hand, it leads to increasing both the NO and the CO2 concentrations.
Keywords: 330; Airblast atomizer; Atomizing air temperature; Spray combustion